THE EFFECT OF THE AMBASSADOR BRAND AND WORD OF MOUTH ON THE HONDA VARIO BRAND AWARENESS at MPM MOTOR NGAGEL - Sholikhah, Shindia Faridatus; Susilowati, Luky (Jurnal Ekonomi Balance, 2021)
At this time companies are competing to determine competitive strategies in order to maintain their products among similar competing companies, namely by instilling brand awareness of their products to potential consumers. Brand awareness is very important so that people know the brand of a product. Brand ambassadors and word of mouth are used by companies in order to increase brand awareness of the product in the minds of consumers.The population in this study is MPM Motor Ngagel consumers who have purchased a Honda Vario in 2020. The sampling method used is random sampling/probability sampling using the Slovin formula. The samples taken were 71 respondents. The data used are primary data and secondary data. While the analysis technique used in this research is Partical Least Square (PLS).Based on the results of the study, it can be seen that Brand Ambassador and Word Of Mouth have a positive and significant effect on Brand Awareness of Honda Vario at MPM Motor Ngagel.